The effect of practicing sports on the body composition and physical fitness of people with intellectual and developmental disabilities - Diz, Susana; Jacinto, Miguel; Costa, Aldo M.; Matos, Rui; Monteiro, Diogo; Teixeira, José E.; Antunes, Raúl (Frontiers in Psychology, 2025)
IntroductionPeople with IDD tend to have a sedentary lifestyle, which affects their health and physical fitness.MethodsThe aim of this study was to analyses the effect of a sport-based intervention, with weekly 60-min sessions over 36 weeks, on the body composition and functional physical fitness of people with Intellectual and Developmental Disabilities (IDD). The sample consisted of 36 institutionalized participants with IDD, divided into two groups: experimental group with 23 participants (M = 37.26; SD = 13.84) and control group with 13 individuals (M = 38.31; SD = 14.22). A stadiometer, bioimpedance equipment and the Hand Grip, Sit and Stand, Timed Up and Go and 6 Min Walk tests were used to assess the variables of interest.ResultsThe experimental group showed statistically significant values in body mass index (p = 0.01; r = 0.301), muscle mass (p < 0.01; r = 0.431), Sit and Stand Test (p = 0.01; r = 0.324) and 6 Min Walk Test (p < 0.01; r = 0.399).DiscussionThe results suggest that long-term programs based on the practice of sports can bring benefits to the body composition and functional physical fitness of adults with IDD.